2015
DOI: 10.1002/rra.2986
|View full text |Cite
|
Sign up to set email alerts
|

Effective Acquisition Protocol of Terrestrial Laser Scanning for Underwater Topography in a Steep Mountain Channel

Abstract: For better risk management, detailed and quantitative measurement of channel and stream‐bed structure is required to understand and predict water and sediment flow in mountain channels. Our previous research demonstrated good performance of green‐wavelength Terrestrial laser scanning (TLS) for measurement of submerged stream‐bed in a steep mountain channel. This paper examines how the acquisition protocol of TLS affects the accuracy of data collected in the mountain channel. First, it was tested whether varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Therefore, to use information of flow condition from flume experiments to predict flood flows, we need the ways to quantitatively measure complex channel morphology (e.g. Miura and Asano, 2015) and further field evidence of the relationship between flow stage and the range of channel elements that control flows.…”
Section: Field Observations and Interpretation Of Flume Experimentsmentioning
confidence: 99%
“…Therefore, to use information of flow condition from flume experiments to predict flood flows, we need the ways to quantitatively measure complex channel morphology (e.g. Miura and Asano, 2015) and further field evidence of the relationship between flow stage and the range of channel elements that control flows.…”
Section: Field Observations and Interpretation Of Flume Experimentsmentioning
confidence: 99%
“…This challenge could be surmounted by using lower‐wavelength (e.g., green) lasers, which are not absorbed so strongly by water and therefore allow for through‐water bathymetry (Friedl et al., 2018). This approach has been trialled by numerous field studies, using both airborne LiDAR (e.g., Hilldale & Raff, 2008; Kinzel & Legleiter, 2019; Kinzel et al., 2007, 2013, 2021; Mandlburger et al., 2015; Pan et al., 2015; Richardson & Moskal, 2014; Tonina et al., 2019; Schwarz et al., 2019) and TLS (e.g., Miura & Asano, 2016; Panagou et al., 2020; Smith & Vericat, 2014; Smith et al., 2012). The TLS approach lends itself well to laboratory landscapes, and has been evaluated by Friedl et al.…”
Section: Topographymentioning
confidence: 99%
“…Monitoring river migration or avulsion lasers, which are not absorbed so strongly by water and therefore allow for through-water bathymetry (Friedl et al, 2018). This approach has been trialled by numerous field studies, using both airborne LiDAR (e.g., Hilldale & Raff, 2008;Kinzel & Legleiter, 2019;Kinzel et al, 2007Kinzel et al, , 2013Kinzel et al, , 2021Mandlburger et al, 2015;Pan et al, 2015;Richardson & Moskal, 2014;Tonina et al, 2019;Schwarz et al, 2019) and TLS (e.g., Miura & Asano, 2016;Panagou et al, 2020;Smith & Vericat, 2014;Smith et al, 2012). The TLS approach lends itself well to laboratory landscapes, and has been evaluated by Friedl et al (2018) and Smith and Vericat (2014); they noted that steep angles of incidence, deep or highly turbid water and rough water surfaces limit the accuracy of laser returns or even the penetration of the laser pulse.…”
Section: Topographymentioning
confidence: 99%
“…All data were collected relatively short ranges (< 20 m). We followed the acquisition protocol outlined by Miura and Asano (2015). For data processing of the acquired TLS data, Leica software program, Cyclone 8.1, generic CAD and Bentley Systems, MicroStation V8 were used.…”
Section: Terrestrial Laser Scanningmentioning
confidence: 99%
“…Our previous research demonstrated good performance of greenwavelength TLS for acquiring underwater data in the pool unit of the channel down to a depth of approximately 70 cm (Miura and Asano, 2013). However, difficulty in acquiring reliable underwater data has been remained in the part of mountain channel where water surface has some gradient (Miura and Asano, 2015). In particular, the existing water-refraction correction method was not applicable in such area because horizontal water surface was a major premise for the method.…”
Section: Introductionmentioning
confidence: 99%